2015
DOI: 10.1037/pro0000039
|View full text |Cite
|
Sign up to set email alerts
|

College students’ perceptions of depressed mood: Exploring accuracy and associations.

Abstract: College is a time of high risk for depressed mood. Theories about depression (i.e. Cognitive Theory and Depressive Realism theory) are well researched, but suggest different venues of understanding the cognitive underpinnings of mood. In addition, much research is available about normative perceptions around substance use and how those perceptions relate to behaviors. However, there are no studies examining normative perceptions around depressed mood nor how these perceptions may relate to students’ own well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For depression, one-item questions are used both among the healthy population and those living with physical conditions:24,25 In the past 2 weeks, have you felt depressed?In the past 30 days, for about how many days have you felt sad, blue?…”
Section: Methodsmentioning
confidence: 99%
“…For depression, one-item questions are used both among the healthy population and those living with physical conditions:24,25 In the past 2 weeks, have you felt depressed?In the past 30 days, for about how many days have you felt sad, blue?…”
Section: Methodsmentioning
confidence: 99%
“…Focusing more on components of protective behavioral strategies may be necessary for this group of student, especially for strategies which may be less salient the highest risk group due to their depression (e.g., obtaining social support from others in non-drinking activities). Finally, correcting normative misperceptions not only around drinking, but also about depressed mood (see Geisner, Kirk, Mittman, Kilmer, & Larimer, 2015a) may help high-risk students reduce their problematic behaviors. It is important to note that normative perceptions appeared to be higher for those who endorsed heavier drinking patterns and may be less associated with depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to increased “helplessness” which may inhibit use of strategies by those who may not use as many protective strategies or try to avoid problems (i.e., not care what happens to them when they drink). In addition, their depressed mood may lead them to misperceiving normative behaviors (Geisner, Kirk, Mittmann, Kilmer, & Larimer 2015). These (less use of PBS and higher normative perceptions) in turn may lead to more drinking and consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies only measured the acquired capability for suicide in terms of the 'fearlessness about death' construct [67,75,77], with one study measuring acquired capability as a suicide-related outcome [78], and a further study measured the thwarted belongingness and perceived burdensomeness constructs but not acquired capability [76]. Ten studies tested theories featuring social norms, including: the Theory of Planned Behaviour [64,65,70,73,74]; the Theory of Reasoned Action [81]; the Theory of Normative Social Behavior [82]; the Social Norms Approach [83,84]; with a further study testing predictions of overestimations of peer depressed mood norms in the context of Beck's Cognitive Theory of Depression [85]. No studies tested both a theory of suicide and a theory of social norms at the same time.…”
Section: Summary Of Identified Literaturementioning
confidence: 99%
“…Not all of the reviewed studies focused on measuring specific suicide-related norms in relation to suicide-related outcomes. Nine studies reported assessing explicit suicide-related norms, such as the perceived prevalence of suicidal behaviour or others' attitudes towards selfharm behaviours or suicidality [64,65,73,74,[82][83][84][85]95]. Sixteen studies focused on the conformity to some form of masculine social norm (e.g., masculine gender roles, masculine sense of honour, traditional or hegemonic norms) [67, 68, 71, 75-79, 90-94, 97-99], with one study focusing on female gender roles in relation to cultural norms associated with childbirth during marriage [72], and one study focusing on the non-conformity to broader traditional gender and sexuality norms amongst LGBT youth [69].…”
Section: Types Of Social Norms Studied In Relation To Nssi/suicidalitymentioning
confidence: 99%